Effectiveness of video assisted teaching program of pranayama on selected physiological parameters among patients with COPD - Harshika Tembhurne; Dipali Dumbre (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: According to research on the global burden of illness, chronic obstructive pulmonary disease (COPD) is expected to rank third globally in terms of cause of mortality in the first 20 years of the 20th century and fifth in terms of major cause of impairment. A thorough yoga program can enhance general well-being and respiratory function, which will improve a person's capacity to complete daily chores. MATERIALS AND METHODS: One group pretest and posttest design in a quasi-experimental study was applied. Collected 50 samples by usingnon-probability sampling method to collect data with the help of tool prepared by researcher. The present study was conducted from April 2022 to June 2023. Analyzed by using Statistical Package for the Social Sciences (SPSS) software. RESULTS: The comparison of pretest and posttest physiological parameters of COPD patients. At the 5% significant level, The Student's paired "t" test is employed, and the mean, standard deviation, and mean difference values are compared. For n = 50-1, or 4 degrees of freedom, the value was 2.00. At the 5% level of significance - a statistically acceptable level of significance - the computed oxygen saturation "t" value, or 29.69, the heart rate (7.16), respiratory rate (16.50), diastolic blood pressure (3.77), and walking distance (15.23), are all significantly greater than the value for general physiological parameters. Thus, the H1 is accepted for oxygen saturation, respiratory rate, and distance in walking. CONCLUSION: Moreover, the study findings highlight the need for ongoing education and outreach efforts to continue improving the health status of COPD patients. This paragraph say that the pranayama is effective in patient with COPD as it help in manageing the illnes and also to improve the lifestyle and also help to im prove the health status of the patient having any other illnesses. In addition, the Compassion of Pranayama and Yoga Pranayama shown effectiveness in daily lifestyle.